2021
DOI: 10.1200/jco.20.03398
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Trastuzumab Emtansine Versus Paclitaxel in Combination With Trastuzumab for Stage I HER2-Positive Breast Cancer (ATEMPT): A Randomized Clinical Trial

Abstract: PURPOSE The ATEMPT trial was designed to determine if treatment with trastuzumab emtansine (T-DM1) caused less toxicity than paclitaxel plus trastuzumab (TH) and yielded clinically acceptable invasive disease-free survival (iDFS) among patients with stage I human epidermal growth factor receptor 2–positive (HER2+) breast cancer (BC). METHODS Patients with stage I centrally confirmed HER2+ BC were randomly assigned 3:1 to T-DM1 or TH and received T-DM1 3.6 mg/kg IV every 3 weeks for 17 cycles or T 80 mg/m2 IV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 33 publications
0
64
0
1
Order By: Relevance
“…The authors of the Adjuvant Paclitaxel and Trastuzumab (APT) Trial suggested that administering adjuvant paclitaxel and trastuzumab to patients with stage I Her2-positive breast cancer represented a de-escalating therapy that preserved quality of life and achieved excellent outcomes for these patients [ 14 , 15 ]. Adjuvant Trastuzumab Emtansine Versus Paclitaxel in Combination with Trastuzumab for Stage I HER2-Positive Breast Cancer (ATEMPT) showed that among patients with stage I HER2-positive breast cancer, one year of adjuvant T-DM1 was associated with excellent 3-year invasive disease-free survival (iDFS) compared with paclitaxel plus trastuzumab [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the Adjuvant Paclitaxel and Trastuzumab (APT) Trial suggested that administering adjuvant paclitaxel and trastuzumab to patients with stage I Her2-positive breast cancer represented a de-escalating therapy that preserved quality of life and achieved excellent outcomes for these patients [ 14 , 15 ]. Adjuvant Trastuzumab Emtansine Versus Paclitaxel in Combination with Trastuzumab for Stage I HER2-Positive Breast Cancer (ATEMPT) showed that among patients with stage I HER2-positive breast cancer, one year of adjuvant T-DM1 was associated with excellent 3-year invasive disease-free survival (iDFS) compared with paclitaxel plus trastuzumab [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized phase II ATTEMPT trial compared the combination of trastuzumab and weekly paclitaxel to antibody–drug conjugate trastuzumab emtansine (T-DM1) in women with stage I HER2 positive breast cancer. The rate of clinically relevant toxicity was similar between the 2 groups (47% vs. 46%) 23 . It is not known if a non-chemotherapy HER2 directed treatment can be used without compromising the outcome of patients with small node negative HER2 positive breast cancer.…”
Section: Discussionmentioning
confidence: 74%
“…In order to further improve these clinical results from APT trial, the ATEMPT trial compared adjuvant T-DM1 and paclitaxel plus trastuzumab in patients with stage I HER2+ BC. TDM-1 was associated with excellent 3-year iDFS, but not with fewer clinically relevant toxicity [59]. Further translational results are anticipated.…”
Section: De-escalating Chemotherapy Drugs: Taxanesmentioning
confidence: 89%